Data, Big and Small: Emerging Challenges to Medical Education Scholarship. (January 2019) - Ellaway, Rachel H.; Topps, David; Pusic, Martin
Abstract : The collection and analysis of data are central to medical education and medical education scholarship. Although the technical ability to collect more data, and medical education's dependence on data, have never been greater, it is getting harder for medical schools and educational scholars to collect and use data, particularly in terms of the regulations, security issues, and growing reluctance of learners and others to participate in data collection activities. These two countervailing trends present a growing threat to the viability of medical education scholarship. In response, there must either be a more conducive data environment for medical education scholarship or medical education must move to become less dependent on data. There is, therefore, a growing need for a system-wide correction: a shift in practice that makes data use more viable and productive while maintaining high professional standards. There are five core areas that can contribute to a system-wide correction: greater clarity over what can be used as data; greater clarity on what constitutes "good" data; changes to the ways in which data are collected; better strategic stewardship of existing data; and deliberate and strategic attention to "data readiness" in support of medical education and medical education scholarship. These solutions are primarily practical and conceptual changes in the face of what are mainly regulatory challenges. However, medical educators also need to engage with emerging areas of practice such as learning analytics, and they need to consider the shifting social contract for using data in medical education.